(untitled) (Journal of Industrial and Mechanical Engineering, 2019)
An integral model of competitive intelligence is applied to meliponini autochthon-honey market for Argentina in 2016. The results of the present study shows potential opportunities for the local Cluster in terms of new high value products and new high tech SMEs creation, specially on sophisticated bio-cosmetic and bio-pharmacy emerging sectors.